EXPERIMENTAL STUDIES ON PARTIAL REPLACEMENT OF NATURAL SAND WITH MANUFACTURED SAND - Thamilselvi, P. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Natural or River sand are weathered particles from rocks which are of various shapes and sizes depending upon the weathering action of rivers. In the present scenario, natural sand with required properties is not easily/locally available. In most of the situations, the natural sand is being brought from faraway places to the construction site.Â Such type of transporting the river sand from faraway places will increase the construction costs. Also these natural river sand is also becoming unavailable due to many reasons. Hence it is very essential to find an alternate material that can substitute the natural river sand either partially or fully. In Tamil Nadu, stone quarries are found in abundance and are wide spread across the state. They are the good source for the coarse aggregate and manufactured fine aggregate. There is a need to make use of the stockpiles of quarry fines generated in those crushers. Hence to make use of these M-sand in the construction industry, a systematic study has to be carried out on the replacement with Natural River sand in making concrete. Experimental investigations carried out on the evaluation of properties of M-sand obtained from different locations (sources) is presented in this paper. Based on the experimental results, mix design for different grades of concrete was carried out using M-sand obtained from two sources by replacement of natural sand. Experimental studies carried out on the properties of fresh and hardened concrete made using the developed mix proportions is also presented in this paper.Â